Evaluation of Temperature Plume Distance under Effects of Groundwater Flow on Borehole Heat Exchanger - Mao Jinfeng; Li Yong; Zhang Hua; Geng Shibin; Han Xu (Zhileng xuebao)
In the ground source heat pump (GSHP) system, the temperature around the borehole heat exchangers (BHEs) would continue to spread further with running time, in addition the groundwater flow would have an important impact on the thermal dispersion. Based on the heat transfer model considering groundwater flow in aquifers, the approximate analytical expression of temperature plume distance was obtained, the factors including groundwater flow velocity，subsurface thermal conductivity and porosity affecting on the temperature plume distance were analyzed by comparing with infinite line source (ILS) model. The results from test platform showed that the temperature plume distance under the groundwater flow velocity was greatly larger than the distance under the pure conductive model and it was different along the axial direction of BHE. In the zone with the groundwater velocity larger than 1×10-6m/s, the distance of 8-10m between the boreholes was recommended for design along the groundwater flow direction.